Optimization and validation of an HS-SPME/GC-MS method for determining volatile organic compounds in dry-cured ham - Babič, Katja; Strojnik, Lidija; Ćirić, Andrija; Ogrinc, Nives (Frontiers in Nutrition, 2024)
The formation of volatile organic compounds (VOCs) in dry-cured ham is a result of different biochemical and enzymatic processes. Moreover, accurately quantifying these VOCs is challenging since ham is a complex matrix, which contains compounds from various chemical families and a wide range of volatilities of different molecular masses. In this study, we systematically optimized and validated an analytical method for quantifying VOCs in dry-cured ham using headspace solid phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS). Optimal SPME conditions were determined through both an experimental procedure (one-factor-at-a-time) and response surface methodology (RSM), revealing that a 60-minute equilibration at 70°C, a 60-minute extraction at the same temperature, and a 4-minute desorption time at 250°C provided the most favorable results. To enhance quantitation, twelve multiple internal standards (ISTDs) were employed to address and improve the quantitation of the 12 VOCs. Method validation covered aspects of linearity, limits of detection (LOD: 0.03-1.13 mg kg-1), limits of quantitation (LOQ: 0.09-3.41 mg kg-1), and working ranges (0.01-19.1 mg kg-1). The practical application of this optimized method was demonstrated by analyzing dry-cured ham samples (n=4), sourced from the Slovenian market.. The initial statistical evaluation indicates that different types of drycured hams can be differentiated (with an 83.1% of accuracy) according to their aromatic profile. However, a larger sample size would be required to provide a more comprehensive assessment.